The Influence Of Market Digitalization, Information Technology Training, And Access To Capital On Income Of Msmes In The Marine Fisheries Firm In Sibolga City - Mega Lusiana Sitorus; Rahmad Sembiring; Suhendi Suhendi (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of market digitalization, information technology training, and access to capital on the income of marine fisheries MSMEs in Sibolga City. This study uses a quantitative method involving 161 respondents. Data collection was carried out using questionnaires. The data obtained were analyzed using statistical formulas, namely by using the normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis with the SPSS Version 23.0 program. The results of this study indicate that the market digitalization variable shows a t-count value of 3.950 > t-table of 1.975 with a significant value of 0.000 <0.05, so the hypothesis H1 is accepted and H0 is rejected, meaning that market digitalization has a positive and significant partial effect on the income of Marine Fisheries MSMEs in Sibolga City. The information technology training variable shows a t-count value of 0.463 < t-table of 1.975 with a significant value of 0.644 > 0.05, so the hypothesis H2 is rejected and H0 is accepted, meaning that information technology training does not have a significant partial effect on the income of Marine Fisheries MSMEs in Sibolga City. The market digitalization variable shows a t-value of 3.128> t-table of 1.975 with a significant value of 0.000 <0.05, so the hypothesis H3 is accepted and H0 is rejected, meaning that access to capital has a positive and significant effect partially on the income of Marine Fisheries MSMEs in Sibolga City. The F-value of 96.246> F-table of 2.66 and a significant value of 0.000 <0.05, so the hypothesis H4 is accepted and H0 is rejected, so it can be concluded that market digitalization, information technology training and access to capital have a positive and significant effect simultaneously on the income of Marine Fisheries MSMEs in Sibolga City.